2009
DOI: 10.1159/000233303
|View full text |Cite
|
Sign up to set email alerts
|

Retention and Silencing of Prepro-GnRH-II and Type II GnRH Receptor Genes in Mammals

Abstract: The decapeptide hypothalamic-pituitary gonadotrophin-releasing hormone (GnRH)-I and the type I GnRH receptor drive the reproductive hormonal cascade in mammals by stimulating synthesis and secretion of luteinising hormone (LH) and follicle stimulating hormone (FSH). Mammals possess a second GnRH system composed of a related hormone, GnRH-II (differing from GnRH-I by three amino acid residues), and the type II GnRH receptor. In many mammalian species, one or both of the GnRH-II system genes are disrupted or del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 140 publications
1
76
0
Order By: Relevance
“…Although there is evidence that the type II GnRHR may mediate behavioral effects of cGnRH-II in the Musk shrew (Kauffman et al, 2005), a functional type II GnRHR has not been reported (Stewart et al, 2009). Nevertheless, ICV infusion of cGnRH-II but not mGnRH stimulated sexual behavior in nutritionally challenged female musk shrews (Temple et al, 2003).…”
Section: Chicken Gnrh-iimentioning
confidence: 94%
See 4 more Smart Citations
“…Although there is evidence that the type II GnRHR may mediate behavioral effects of cGnRH-II in the Musk shrew (Kauffman et al, 2005), a functional type II GnRHR has not been reported (Stewart et al, 2009). Nevertheless, ICV infusion of cGnRH-II but not mGnRH stimulated sexual behavior in nutritionally challenged female musk shrews (Temple et al, 2003).…”
Section: Chicken Gnrh-iimentioning
confidence: 94%
“…In the mature male Zebra finch (Taeniopygia guttata) the number of cGnRH-II neurons is significantly reduced during the non-breeding season as compared with the breeding season (Perfito et al, 2011 (Kauffman and Rissman, 2004a). However, this information is questionable due to the lack of a functional cGnRH-II peptide and the lack of a functional type II GnRHR in mice (Stewart et al, 2009). Among primates, the rhesus monkey (Macaca mulatta), is one of the few species studied to date that posses a functional cGnRH-II peptide and type II GnRHR (Stewart et al, 2009).…”
Section: Chicken Gnrh-iimentioning
confidence: 99%
See 3 more Smart Citations